PELAKSANAAN PEMBELAJARAN DI TPQ SURAU RUNCING DESA TIMBULUN KENAGARIAN SURANTIH KABUPATEN PESISIR SELATAN - Zeris Dewindo (Universitas Negeri Padang, 2014)
This research is backgrounded by successful TPA this even out learning process, visually of acquired achievement per annum, oldster support and citizen motivation studies that excelsior. This research intent to figure Learning Performing at TPA Desa Timbulun Kenagarian Surantih Kabupaten Pesisir Selatan that is seen from material aspect studies, learned method, learned atmosphere, learned source and studying media. This observational type is observational descriptive quantitative, with subjek citizen research at TPA Desa Timbulun Kenagarian Surantih Kabupaten Pesisir Selatan. Its research result is a large part citizen study to declare for is motivated and understanding clearly material studies, learned method, learned atmosphere, learned source and studying media for citizen studies TPA Surau Runcing